2021
DOI: 10.13057/biodiv/d220149
|View full text |Cite
|
Sign up to set email alerts
|

Riparian plant diversity in relation to artisanal mining sites in Cikidang River, Banten, Indonesia

Abstract: Abstract. Takarina ND, Sinaga IL, Kultsum TR. 2021. Riparian plant diversity in relation to artisanal mining sites in Cikidang River, Banten, Indonesia. Biodiversitas 22: 401-407. Artisanal mining usually occurs in gold mining activities near the river banks and consequently, this will affect the downstream ecosystem include riparian habitat and its plant diversity. Here, this study aimed to assess the effects of artisanal mining sites on the riparian plant diversity in Cikidang River, Lebak District, Banten P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, small-scale gold mining activities can reduce the diversity of riparian plants in the vicinity. Takarina et al (2021) confirmed that areas near gold mining only contributed 26.1% of the 42 riparian species on the Cikidang River in Lebak (Banten, Indonesia). In Pancurendang, Banyumas, Indonesia several species of herbaceous plants were found nearby gold tailing deposits at location number 6: I. aquatica, L. perennis, C. esculenta, D. longiflora, M. vaginalis, and L. flava, which were categorized as resistant to the heavy metals found in the tailings.…”
Section: Diversity Of Herbaceous Plant Species In Gold Mining and Pro...mentioning
confidence: 65%
See 1 more Smart Citation
“…Therefore, small-scale gold mining activities can reduce the diversity of riparian plants in the vicinity. Takarina et al (2021) confirmed that areas near gold mining only contributed 26.1% of the 42 riparian species on the Cikidang River in Lebak (Banten, Indonesia). In Pancurendang, Banyumas, Indonesia several species of herbaceous plants were found nearby gold tailing deposits at location number 6: I. aquatica, L. perennis, C. esculenta, D. longiflora, M. vaginalis, and L. flava, which were categorized as resistant to the heavy metals found in the tailings.…”
Section: Diversity Of Herbaceous Plant Species In Gold Mining and Pro...mentioning
confidence: 65%
“…Chamba et al (2017) stated that Erato polymnioides from this family, which is associated with mycorrhizae, is a potential Hg hyperaccumulator plant. Grasses, which make up Poacea (Aitken et al 2014), are known to survive in unfavorable soil conditions, be resistant and adaptable to heavy metals, and have deep roots (Khodijah et al 2019;Takarina et al 2021).…”
Section: Diversity Of Herbaceous Plant Species In Gold Mining and Pro...mentioning
confidence: 99%
“…A high riparian tree diversity may be associated with high oxygen levels in rivers and streams, which serve as clean water resources (ecosystem service) for human and livestock (Luke et al 2018). However, due to some concerning anthropogenic activities, the diversity of riparian vegetation is being threatened as documented in previous studies in human-altered sites (Izzati and Hasibuan 2019;Takarina et al 2021). Rubber (Hevea brasiliensis) was documented as the highest IVI for tree stage in Barumun River.…”
Section: Importance Value Index (Ivi) Of the Vegetation Structure In Barumun Watershedmentioning
confidence: 90%
“…Low riparian diversity was also correlated with nutrient inputs from the surrounding lands. The richness of riparian communities and environmental variability may be explained by high levels of eutrophication [16]. The total riparian vegetation cover, cover structure, cover quality, and channel changes make up the QBR index, which is based on these four aspects of riparian habitat.…”
Section: Profile Of Riparian Tree On Waterfalls and Springs In Bawean...mentioning
confidence: 99%